The Prevalence of Insomnia, Its Demographic Correlates, and Treatment in Nurses Working in Chinese Psychiatric and General Hospitals. Issue 2 (30th January 2015) - An, Feng‐Rong; Qi, Yun‐Ke; Zeng, Jiao‐Ying; Ding, Yan‐Ming; Chiu, Helen F. K.; Ungvari, Gabor S.; Newhouse, Robin; Yu, Doris S. F.; Lai, Kelly Y. C.; Xiang, Yu‐Tao
Abstract : Purpose: To determine the prevalence of insomnia and its socio‐demographic correlates in Chinese nurses. Design and Methods: Up to 799 nurses were examined. Demographic data, total sleep time (TST), and insomnia were collected. Findings: The mean expected and actual TST were 8.3 ± 1.5 and 6.1 ± 1.1 hr, respectively. The prevalence of at least one type of reported sleep disturbance was 69.7%; the rates of difficulty initiating sleep, difficulty maintaining sleep, and early morning awakening were 54.6%, 54.7%, and 55.9%, respectively. Practice Implications: There is a large discrepancy of actual and expected sleep duration, and insomnia is common among nurses in China.